2022
DOI: 10.1186/s12909-021-03062-3
|View full text |Cite
|
Sign up to set email alerts
|

All-digital training course in neurophysiology: lessons learned from the COVID-19 pandemic

Abstract: Background The social distancing and suspension of on-campus learning, imposed by the COVID-19 pandemic, are likely to influence medical training for months if not years. Thus, there is a need for digital replacement for classroom teaching, especially for hands-on courses, during which social distancing is hardly possible. Here, we investigated students’ learning experience with a newly designed digital training course in neurophysiology, with intercalated teaching blocks in either asynchronous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Duszenko et al reported that some students faced technical difficulties and poor interaction between group members during online group work. Accordingly, 54% of students opposed the notion that online teamwork helped them understand the topic [ 11 ]. Furthermore, Kalmar et al found that students reported lowered productivity in group work and difficulty in receiving feedback from peers after switching to online education [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Duszenko et al reported that some students faced technical difficulties and poor interaction between group members during online group work. Accordingly, 54% of students opposed the notion that online teamwork helped them understand the topic [ 11 ]. Furthermore, Kalmar et al found that students reported lowered productivity in group work and difficulty in receiving feedback from peers after switching to online education [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant difference was found, these findings confirm that the adopted e-course was at least as effective for content knowledge as our pre-COVID face-to-face course. Duszenko et al reported that none of the e-learning instructed students performed worse than their face-to-face instructed colleagues [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations